Efektivitas Modul Elektronik Berbasis Web Dipadu Problem Based Learning Terhadap Motivasi Belajar pada Materi Pencemaran Lingkungan - Della Moliza Karlina; Andi Ulfa Tenri Pada*; Khairil Khairil; Wiwit Artika; Abdullah Abdullah (Jurnal Pendidikan Sains Indonesia, 2021)
The teaching and learning activities at grade 10th SMA Negeri 1 Krueng Barona Jaya and SMAN 1 Peukan Bada Aceh Besar, it can be seen that the learning motivation of students is still lacking to learn. The learning motivation of students has not been maXmized because students still feel the learning conditions that provide opportunities for students to make assumptions and carry out an experiment to obtain their own knowledge. This condition causes students to only refer to conventional modules which contain material only. This study aims to analyze the differences in the learning motivation of students in the experimental class and the control class on environmental pollution material in class grade 10th  SMAN Aceh Besar. The approach used in this research is quantitative, the type of research is applied research, a quasi-experimental method, with a pretest-posttest non-equivalent control group design. The research sample was 105 students. The research procedure was to provide a pre-test, a web-based electronic module treatment combined with PBL in the experimental class and conventional methods in the control class, and post-test. The instrument used is a questionnaire that has been tested for validity, reliability test. Data analysis used independent t-test with prerequisite test for normality and homogeneity test. The results showed that there were differences in the learning motivation of students in the experimental class and the control class on environmental pollution concept in class X SMAN Aceh Besar. The learning motivation taught by web-based electronic modules combined with PBL is better than conventional methods.